Biodegradable Magnesium‐Based Implants in Orthopedics—A General Review and Perspectives. Issue 8 (28th February 2020) - Wang, Jia‐Li; Xu, Jian‐Kun; Hopkins, Chelsea; Chow, Dick Ho‐Kiu; Qin, Ling
Abstract: Biodegradable Mg‐based metals may be promising orthopedic implants for treating challenging bone diseases, attributed to their desirable mechanical and osteopromotive properties. This Review summarizes the current status and future research trends for Mg‐based orthopedic implants. First, the properties between Mg‐based implants and traditional orthopedic implants are compared on the following aspects: in vitro and in vivo degradation mechanisms of Mg‐based implants, peri‐implant bone responses, the fate of the degradation products, and the cellular and molecular mechanisms underlying the beneficial effects of Mg ions on osteogenesis. Then, the preclinical studies conducted at the low weight bearing sites of animals are introduced. The innovative strategies (for example, via designing Mg‐containing hybrid systems) are discussed to address the limitations of Mg‐based metals prior to their clinical applications at weight‐bearing sites. Finally, the available clinical studies are summarized and the challenges and perspectives of Mg‐based orthopedic implants are discussed. Taken together, the progress made on the development of Mg‐based implants in basic, translational, and clinical research has laid down a foundation for developing a new era in the treatment of challenging and prevalent bone diseases. Abstract : This Review summarizes the current status and future research trends for Mg‐based or containing orthopedic implants. The progress made on the development of Mg‐based or containing implants in basic, translational, and clinical research can lay down a foundation for opening a new era to improve clinical healing outcomes in the treatment of challenging bone diseases.